Comparative analysis of the discrepancy in conventional cephalometric tracing and digital cephalometric tracing with Planmeca Romexis® software = Análisis comparativo de la discrepancia en trazado cefalométrico convencional y trazado cefalométrico digital con el software Planmeca Romexis® - Chinchilla Torres, Pamela 1995-
The objective of this study was to compare the discrepancy in conventional cephalometric tracing and digital cephalometric tracing in lateral skull radiographs, with 3 angular and 3 linear measurements. We used 24 digital lateral skull radiographs of patients from the Universidad Latina de Costa Rica, taken with the Kodak 8000C Digital Panoramic and Cephalometric System, for the computerized tracing the radiographs were passed directly to the Planmeca Romexis® software, and the same radiographs were printed for the manual tracing. A comparison between the manual tracing and the Planmeca Romexis® software measurements showed statistically significant differences (p<0,05) of 4 measurements between the two systems. It is evident that the cephalometric tracing with the Planmeca Romexis® software is more reliable than the manual tracing due to the data obtained in this research.